Rare genetic variants in interleukin-37 link this anti-inflammatory cytokine to the pathogenesis and treatment of gout. Issue 4 (29th February 2020) - Klück, Viola; van Deuren, Rosanne C; Cavalli, Giulio; Shaukat, Amara; Arts, Peer; Cleophas, Maartje C; Crișan, Tania O; Tausche, Anne-Kathrin; Riches, Philip; Dalbeth, Nicola; Stamp, Lisa K; Hindmarsh, Jennie Harré; et al.
Abstract : Objective: Gout is characterised by severe interleukin (IL)-1-mediated joint inflammation induced by monosodium urate crystals. Since IL-37 is a pivotal anti-inflammatory cytokine suppressing the activity of IL-1, we conducted genetic and functional studies aimed at elucidating the role of IL-37 in the pathogenesis and treatment of gout. Methods: Variant identification was performed by DNA sequencing of all coding bases of IL37 using molecular inversion probe-based resequencing (discovery cohort: gout n=675, controls n=520) and TaqMan genotyping (validation cohort: gout n=2202, controls n=2295). Predictive modelling of the effects of rare variants on protein structure was followed by in vitro experiments evaluating the impact on protein function. Treatment with recombinant IL-37 was evaluated in vitro and in vivo in a mouse model of gout. Results: We identified four rare variants in IL37 in six of the discovery gout patients; p.(A144P), p.(G174Dfs*16), p.(C181*) and p.(N182S), whereas none emerged in healthy controls (Fisher's exact p-value=0.043). All variants clustered in the functional domain of IL-37 in exon 5 (p-value=5.71×10 −5 ). Predictive modelling and functional studies confirmed loss of anti-inflammatory functions and we substantiated the therapeutic potential of recombinant IL-37 in the treatment of gouty inflammation. Furthermore, the carrier status of p.(N182S)(rs752113534) was associated with increased risk (OR=1.81, p-value=0.031) of developing gout in hyperuricaemic individuals of Polynesian ancestry. Conclusion: Here, we provide genetic as well as mechanistic evidence for the role of IL-37 in the pathogenesis of gout, and highlight the therapeutic potential of recombinant IL-37 for the treatment of gouty arthritis.